Memórias de um autor em construção: reinvenção de processos criativos como fonte de aprendizado - SILVA NETO, Alberto da Cunha e (Universidade Federal do Pará, 2017)
This paper presents a mapping of four creative process experienced by the researcher, conducted with the aim of understanding the acquired knowledge about the art of acting and how it was built from these practices. Based on the notion of memory as a reinvention of living, using the concept of Amazon behavior as methodology, and from the theoretical framework on the psychophysical actions as the basis for the work of the actor, was made a critical analysis of techniques, procedures and constructive methods used or produced in these process, which results in the invention of these methods from a current look. The result of this research extends the researcher‟s view about the actor, dilated to understand the mind of the actor as a source of fluid sheet stock psychophysical, generating knowledge that can be applied in future performances, theatrical directions, and the other practices in theatre theory and interpretation teaching, and contribute to the theoretical studies about the actor from the experience of creation.